When Human Behavior Challenges the Data: Strategic Interaction and Response Shift as Threats o Validity in Clinical Research - Carretero, Marcelina (Revista del Hospital Italiano de Buenos Aires, 2025)
In clinical research, the validity of results can be compromised by classical factors such as bias, confounding, and sampling error. However, there are  other elements related to human behavior that are not always considered and can also affect the conclusions. This article explores two such phenomena: strategic interaction and response shift. The former occurs when individuals adjust their behavior based on what they believe others will do. The latter refers to a change in how people evaluate their own health over time. Through everyday examples –such as penalty kicks in football, traffic decisions, or self-reported quality of life– we examine how these dynamics can impact the validity of clinical studies. Recognizing these mechanisms is essential for accurately interpreting results and  designing methodological strategies to minimize their influence.
Keywords: Strategic Interaction; Behavioral Bias; External Validity; Internal Validity; Response Shift